Guardamonte, between Dig and Promotion of an Elevated Place Settlement between Piedmont and Lombardy (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2014)
The archeological site of Guardamonte is an hillfort, or elevated place settlement, placed between the department of Lombardy and Piedmont, and divided between the district of Gremiasco, Cecima and Ponte Nizza. The settlement started since Middle Neolithic Age and persisted, despite some hiatus, till the Roman Age, but the most important period is the II Iron Age. The research of the team of Preroman Archeology permitted the reconstruction of the site and its diffusion to the public.
Keywords: Guardamonte; Gremiasco; Cecima; Ponte Nizza; hillfort; ligurian; Iron Age